Power factor correction in power systems having load asymmetry by using fuzzy logic controller - Tanrioven, M; Kocatepe, C; Unal, A (SPRINGER-VERLAG BERLIN, 1997)
As known, the studies on power factor correction have been carried out for many years. But in these studies, generally, phase powers received from supply are assumed to be balanced. In the paper, power systems having unbalanced load are considered. The fuzzy logic controller based on the fuzzy set theory provides a useful tool for converting the linguistic control from the expert knowledge into automatic control rules. By using fuzzy automatic rules from the heuristic or mathematical strategies, complex processes can be controlled effectively in many situations.[1] But the most important and difficult point is how to obtain the proper control rules for a given system. In this paper, power factor correction is corrected to demand value by using fuzzy logic controller for the electric power system containing current unbalance i.e. load asymmetry. As well as this, generalized fuzzy logic controller was resembled by writing its software in Q - basic programming language. Consequently, the software of the system's simulation results were given for power factor correction in the power systems having load asymmetry. In addition to that, the developed method is compared according to conventional compensation systems.
Keywords: Computer Science